Marriage Dispensation: An Analysis from the Perspective of Islamic Marriage Law and the Sustainable Development Goals - afif muamar; Tohayudin; Adang Djumhur; Muhammad Feby Ridho Pangestu (Asy-Syir'ah: Jurnal Ilmu Syari'ah dan Hukum, 2024)
This article examines the implementation of marriage dispensation law in Religious Courts from the perspective of marriage law and the Sustainable Development Goals (SDGs), which often appear to be in conflict. Using a normative and sociological approach with qualitative analysis, this article finds that marriage dispensation, from the perspective of marriage law, is solely intended to serve the best interests of the child. It is a measure that must be carefully considered to ensure the child's protection, care, well-being, survival, and development. However, from the SDGs perspective, marriage dispensation may pose a threat or obstacle to achieving sustainable development goals, which aim to cultivate a reliable, resilient, and high-quality generation. The differing perspectives on marriage dispensation create an apparent contradiction between legal norms and sustainable development objectives. Nevertheless, these perspectives can be harmonized by recognizing that the goals of the SDGs and legal principles ultimately align. Thus, marriage dispensation should not always be viewed as a conflict between legal norms and societal realities. This divergence can be reconciled through court decisions that position marriage dispensation cases as das sein (facts/reality) and the SDGs' objectives as das sollen (ideals and aspirations). Artikel ini mengkaji penerapan hukum dispensasi kawin di Pengadilan Agama dari perspektif hukum perkawinan dan tujuan SDGs yang sering kali tampak saling bertentangan. Menggunakan pendekatan normatif dan sosiologis dengan analisis kualitatif, artikel ini menemukan bahwa dispensasi kawin dalam sudut pandang hukum perkawinan semata-mata untuk kepentingan terbaik anak, yaitu tindakan yang harus dipertimbangkan untuk memastikan perlindungan, pengasuhan, kesejahteraan, kelangsungan hidup dan tumbuh kembang anak. Sementara dalam perspektif SDGs, dispensasi kawin bisa menjadi salah satu ancaman atau penghambat bagi terwujudnya tujuan pembangunan yang berkelanjutan, yang hendak mempersiapkan generasi yang handal, kuat dan berkualitas. Sudut pandang yang berbeda dalam melihat dispensasi kawin tersebut menjadikan keduanya seolah saling bertentangan. Namun demikian, keduanya sebenarnya bisa diharmonisasikan dengan menyatukan persepsi bahwa antara tujuan SDGs dan tujuan hukum adalah satu kesatuan. Dengan demikian, dispensasi kawin tidak selalu harus dipertentangkan antara norma hukum dan realitas yang ada dalam masyarakat. Kenyataan tersebut bisa dijembatani melalui keputusan pengadilan, yang mendudukan kasus dispensasi kawin sebagai das sein (fakta/realita), dan tujuan SDGs sebagai das sollen (cita-cita dan harapan).